ENTREPRENEURSHIP AND FINANCIAL MANAGEMENT TRAINING FOR INDONESIAN MIGRANT WORKERS AS PREPARATION FOR RETURNING HOME - DEWI, MONICA; Krissanya , Nofriska; Suherman, Suherman; Buchdadi , Agung Dharmawan; Az-Zahra, Ridya; Danapati, Muhammad Ridho; Setyawan, Rahmat Dika (Yayasan Education and Social Center, 2025)
The Entrepreneurship and Financial Management Training for Indonesian Migrant Workers as Preparation for Returning Home program was designed to enhance the financial literacy and entrepreneurial capacity of Indonesian migrant workers in Tainan, Taiwan. This initiative responds to the financial challenges commonly faced by migrant workers, particularly in managing income, planning investments, and ensuring economic stability upon returning to Indonesia. Using a participatory approach that includes needs assessment, interactive lectures, financial planning simulations, and digital technology training, the program equips participants with practical skills in budgeting, saving, risk mitigation, and business planning. Evaluation results indicate increased understanding across participant groups with different characteristics, including gender, age, education level, and length of employment. Participants with longer work experience and higher educational backgrounds tended to achieve higher scores, although the program proved effective for all groups. These findings demonstrate that structured and context-based training can significantly improve the financial preparedness and entrepreneurial potential of migrant workers as they reintegrate economically upon returning home. The program also contributes to community empowerment and promotes inclusive economic development